Answer:
hviygkcgc fgx
Step-by-step explanation:
Answer:
x = - 10
Step-by-step explanation:
Express the fractions on the left side as a single fraction.
Multiply the numerator/denominator of the first fraction by (x - 2)
Multiply the numerator/denominator of the second fraction by (x + 1)
+
= 3
Distribute the numerators and simplify
= 3 ( cross- multiply )
3x² - 2x + 4 = 3(x+ 1)(x - 2) ← distribute
3x² - 2x + 4 = 3(x² - x - 2)
3x² - 2x + 4 = 3x² - 3x - 6 ( subtract 3x² - 3x from both sides )
x + 4 = - 6 ( subtract 4 from both sides )
x = - 10
<u>Solution</u><u>:</u> 9:x = x:4
⇛9/x = x/4
By doing cross multiplication, we get
⇛9(4) = x(x)
⇛36 = x²
⇛x² = 36
⇛x = √(36)
⇛x = √(6*6)
∴ x = 6 Ans.
<u>also</u><u> read</u><u> similar</u><u> questions</u><u>:</u><u> </u>Which equations have the same value of x as 2/3(6x+12)=-24? Check all that apply.1. 4x+8=24 2. 9x+18=-24 3. 4x+12=-24 4. 18x+36/2=-24 5. 4x=-36 6. 4x=-32 7. x=-... brainly.com/question/6702722?referrer